1954
DOI: 10.1161/01.cir.9.3.416
|View full text |Cite
|
Sign up to set email alerts
|

Stages of Salt Exchange in Essential Hypertension

Abstract: The relation of sodium to hypertension remains one of the most fascinating problems in medicine.The results accumulated over a five-year period of study of this relationship are presented in the paper which follows. In these investigations the appetite for salt and the output of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1954
1954
1986
1986

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…2 We subsequently showed that the tendency of hypertensive patients toward increased sodium excretion could be elicited not only by hypertonic saline loads, but by mannitol and isotonic saline loads as well. 3 A lower, but still significant, correlation between the blood pressure of patients and their urinary sodium output was also demonstrated under basal conditions.' In comparable animal studies we had found that the basal output of sodium was directly proportional to its antecedent intake in the diet.…”
mentioning
confidence: 91%
“…2 We subsequently showed that the tendency of hypertensive patients toward increased sodium excretion could be elicited not only by hypertonic saline loads, but by mannitol and isotonic saline loads as well. 3 A lower, but still significant, correlation between the blood pressure of patients and their urinary sodium output was also demonstrated under basal conditions.' In comparable animal studies we had found that the basal output of sodium was directly proportional to its antecedent intake in the diet.…”
mentioning
confidence: 91%
“…The explanation has been offered that this excretory derangement is related to alterations in renal function and that the high salt excretors were those hypertensive subjects whose renal plasma flow was reduced and filtration fraction elevated. 8 Others,5' 6 however, have failed to observe such a relationship between increased sodium output and renal hemodynainics. The parallelism of the sodium clearance with both the level of the blood pressure2 4-6 9, 10 and renal vascular resistance6 suggested to This work is supported by the Johln A. Hartford Foundation and the Eda K. Loeb Fund.…”
mentioning
confidence: 99%
“…Whereas three of the subjects manifested an exaggerated natriuresis, the remaining two manifested responses not differing from that of normal subjects. Green et al 7 studied renal sodium and water handling in 26 nonhypertensive controls and 53 patients with hypertension and observed that the hypertensive patients could be divided into a "normal sodium-excreter" group and a "high sodium-excreter" group (« = 18). During the saline infusion test, the high sodium-excreter group excreted sodium at a mean rate of 535 ± 182 /xEq/min, a level approximately threefold greater than that of the normal sodium-excreter hypertensive subjects.…”
Section: Discussionmentioning
confidence: 99%